Inequality and Radicalisation: Systematic Review of Quantitative Studies - Franc, Renata (Terrorism and political violence, 2023)
This systematic review sought to synthesize and evaluate the quantitative findings regarding the inequality-radicalization relationship while considering their multidimensionality. The comprehensive search resulted in the screening of more than 5,000 items and the final inclusion of 141 publications. The findings of narrative synthesis suggested that socio-political inequality is more consistently positively related to terrorism/cognitive radicalization than economic inequality, which is more relevant for behavioral radicalization. The findings are discussed in terms of the importance of differentiating between dimensions, indicators, and levels of inequality and radicalization, complex relations, as well as shortcomings of existing evidence base and opportunities for improvement.